Is histologic esophagitis associated with dental erosion: a cross-sectional observational study? - Lynn Roosa Friesen; Brenda Bohaty; Robin Onikul; Mary P. Walker; Caren Abraham; Karen B. Williams; Jose T. Cocjin; Eileen L. Cocjin; Craig A. Friesen (BMC Oral Health, 2017)
Abstract Background Gastroesophageal reflux disease (GERD) affects 15–25% of children and adolescents in the United States. The diagnosis of GERD in children is complex as reported symptoms or symptom profiles have been found to be unreliable. Frequently, the diagnosis must be confirmed by objective tests such as pH monitoring or histological evidence of esophagitis on an esophageal biopsy. Dental erosion has been shown to be associated with GERD as an atypical complication and has the potential to be a marker of GERD. The purposes of this study were to compare the frequency and patterns of dental erosion in children and adolescents with and without histologic esophagitis. Methods Twenty-five subjects were recruited from patients scheduled for an upper gastrointestinal endoscopy. Information regarding potential GERD symptoms, food habits, and dental hygiene habits were obtained. Intra-oral photographs were taken, and a dental exam for erosion was performed. The results of a standard biopsy taken from the lower third of the esophagus during an endoscopy were used to divide subjects into either the control group or the GERD group (i.e. those with histologic esophagitis). Results Twenty-two subjects yielded 586 evaluable teeth. No significant difference was found between frequency or erosion patterns of those with and without histologic esophagitis. Dental erosions were more frequent in primary teeth. Conclusions Dental erosions do not appear to be associated with histologic esophagitis indicative of GERD.